Analysis of the DNA-binding activity of p53 mutants using functional protein microarrays and its relationship to transcriptional activation - Malcikova, Jitka; Tichy, Boris; Damborsky, Jiri; Kabathova, Jitka; Trbusek, Martin; Mayer, Jiri; Pospisilova, Sarka (Biological chemistry, 2010)
Sequence-specific DNA binding is the key function through which tumor suppressor p53 exerts transactivation of the downstream target genes, often being impaired in cancer cells by mutations in the TP53 gene. Functional protein microarray technology enables a high-throughput parallel analysis of protein properties within one experiment under the same conditions. Using an array approach, we analyzed the DNA binding activity of wild type p53 protein and of 49 variants. Our results show significant differences in the binding properties between the p53 mutants. The C-terminal mutant R337C displayed the highest DNA binding activity on the array. However, the same mutant showed only a partial activation in the reporter gene assay and almost no activation of downstream target genes after transfection of expression vector into cells lacking endogenous p53. These observations demonstrate that DNA binding itself is not sufficient for activating the p53 target genes in at least some of the p53 mutants and, therefore, in vitro studies might not always reflect in vivo conditions.
Keywords: polymerázová řetězová reakce s reverzní transkripcí; nádorové buněčné linie; Cell Line, Tumor; lidé; Humans; Mutation; Genetic Variation; genetická transkripce; Binding Sites; molekulární modely; aktivace transkripce; Transcriptional Activation; DNA; genetická variace; nádorový supresorový protein p53; Reverse Transcriptase Polymerase Chain Reaction; Mutant Proteins; čipová analýza proteinů; Protein Array Analysis; vazebná místa; Tumor Suppressor Protein p53; Transcription, Genetic; mutace; mutantní proteiny; Models, Molecular